Feeding selenium-rich fermented palm kernel cake to laying hens produces selenium-rich eggs, increases egg production and quality - B. Sundu; H. Hafsah; M. Pamulu; A. Adjis; U. Hatta; E. Kala’langi; G. Sapu; S. Arifuddin; D. Damry; I. G. Putra (Journal of the Indonesian Tropical Animal Agriculture, 2023)
A study was conducted to determine the effect of selenium (sodium selenite) added to palm kernel cake (PKC) before fermentation on production, selenium content, and quality of eggs. The PKC was added with 0.1% sodium selenite and 1% baking yeast (Fermipan®). The mixture was added with ster-ile distilled water to increase the water content of the substrate. The substrates were fermented at room temperature for 5 days. The fermented products of selenium-rich fermented palm kernel cake (SRFPKC) were dried and fed to the laying hens. The experimental diets used were T-0: without SRF-PKC, T-1: 0.25% SRFPKC, T-2: 0.50% SRFPKC, T-3: 0.75% SRFPKC and T-4: 1.0 % SRFPKC. The diets were given to 180 laying hens aged 22 weeks for 14 weeks. Data on egg production, feed intake and feed conversion ratio were recorded. Feed digestibilities of dry matter and protein were measured based on the method of total fecal collection. Egg qualities and egg weight loss were done using eggs stored for 1 and 30 days. Selenium and cholesterol contents of eggs were also measured. This study used a completely randomized design and was analyzed by analysis of variance. The results showed that the addition of SRFPKC increased egg production, hen day, egg weight, egg selenium, feed digest-ibility, improve FCR (P<0.05) and inhibit the process of decreasing the quality and weight of eggs stored for 30 days (P<0.05). In conclusion, the addition of SRFPKC increased egg production, feed digestibility, and egg selenium, improve FCR and slow down the deterioration of egg quality stored for 30 days.